Serum steroid and thyroid hormone concentrations in healthy domestic male and female alpacas - Fecteau, Kellie; Giori, Luca; Eiler, Hugo; Esteller-Vico, Alex; Lear, Andrea; Videla, Ricardo (Frontiers in Veterinary Science, 2023)
Alpacas are high quality fiber producing animals, kept for production purpose and as pets.Endocrine imbalances from adrenal glands, gonads, or thyroid gland may result in coat abnormalities in domestic animals and affect reproduction. Contrary to many domesticated animals, information on hormone concentrations in alpacas is scarce. The purpose of this study was to provide steroid and thyroid hormone values in domestic alpacas. Blood was collected from healthy male (35 intact, 2 castrated) and female (48 non-pregnant, 3 pregnant) alpacas from local farms in Tennessee. Adrenal, reproductive, and thyroid hormones were analyzed. There were no significant differences in median concentrations of progesterone, estradiol, thyroxine (T4), and triiodothyronine (T3) between intact male and female non-pregnant alpacas. Median concentrations of testosterone, androstenedione, 17-hydroxyprogesterone, and cortisol were significantly higher in intact male alpacas compared to female non-pregnant alpacas. This information provides adrenal, gonadal, and thyroid hormone concentrations in alpacas to help with diagnosis of endocrine disorders.